Sustainable benefits to sugarcane farmers through a strong ethanol blending programme in India - Roy, M. M.; Chandra, A. (Indian Farming, 2018)
A stable ethanol blending programme in the country will ensure sustainable benefits to the sugarcane farmers, who are frequently affected in bumper sugarcane crops and its lack of market demand. Such incentives will motivate small- and medium-farmers to increase their efforts towards scientific management sugarcane of crop as there will be better returns.